Oral History at a Distance. - Sielaff, Steven; Sloan, Stephen M.; Cain Darough, Adrienne A.; Holland, Michelle (Oxford : Taylor & Francis Group, 2024)
Oral History at a Distance is the first publication to explore both the ideas behind and application of oral history in remote projects.
Cover -- Half Title -- Series -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- Foreword -- Preface -- Section I Chapters -- 1 Introduction -- 2 Project Design -- 3 Ethical Considerations for Remote Projects -- 4 Managing Remote Projects -- 5 Interviewing at a Distance -- 6 Remote Recording Technology -- 7 Preserving Remote Recordings -- 8 Looking Ahead: Final Thoughts on Going Remote -- 9 Afterword -- Section II Case Studies -- 10 Interviewing Remotely: The Vietnam Center and Archive Oral History Project as a Case Study -- 11 The Utica Roots Oral History Project -- 12 Bridging Distance in Project-Based Research: The Cases of "Montreal Life Stories" and "Deindustrialization and the Politics of Our Time" -- 13 Moving Past "Analog" Remote Recording: Total Recorder, TheirStory, and the UW-Madison (Wisconsin) Oral History Program -- 14 A Community Connecting during a Pandemic: Case Study for Oral History at a Distance -- 15 Pivoting in Crisis: The Arthur Ashe Oral History Project at UCLA -- 16 Oral History at a Distance: A View from Australia -- 17 National Life Stories -- 18 TheirStory: How a Visit to the Anne Frank House Resulted in the Creation of an Oral History Platform -- Section III "Oral History at a Distance" Webinar Survey -- Section IV Appendix -- 19 Sample Project Design -- 20 Sample Memorandum of Understanding -- 21 BUIOH Cost Schedule for Oral History Interviewing and Processing -- 22 BUIOH Interviewer Deed-of-Gift Agreement -- 23 BUIOH Interviewee Deed-of-Gift Agreement -- 24 BUIOH Restricted Interviewee Deed-of-Gift Agreement -- 25 Sample BUIOH Interview Abstract -- 26 Sample BUIOH Interview Audio Log -- 27 BUIOH Transcription Assistant Contract -- 28 BUIOH Equipment Loan Agreement -- 29 BUIOH Email Template for Transcript Review Request -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books